MENINGKATKAN PENGETAHUAN DAN KESEHATAN LANSIA TENTANG HIPERTENSI DENGAN METODE PENYULUHAN KESEHATAN - Noviati, E.; Kusumawanty, J.; Rahmawati, I.; -, Rosmiati; Marliany, H.; Kurniawan, R. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana Mengabdi, 2022)
Hypertension is a major risk factor for chronic disease and death. Based on the household health survey, there are 26.3% of hypertension sufferers spread throughout Indonesia. Based on WHO data from 100% of hypertensive patients, only 25% received treatment, and only 12.5% received good treatment. The purpose of this service is to increase the knowledge of the elderly about hypertension and increase the ability of the elderly to prevent complications of hypertension. Partners in this service activity are elderly posyandu cadres in the Rancapetir neighborhood, Ciamis district. This service was attended by 12 participants, namely elderly people with hypertension. The service methods carried out include blood pressure checks, lectures, discussions and questions and answers. Community service went smoothly, all participants were committed to implementing all the recommendations given by the resource persons.   Keywords: Elderly, Hypertension, Stroke